PEMBUATAN TEPUNG SERAT TINGGI DARI AMPAS KELAPA (COCOS NUCIFERA) DENGAN METODE PENGERINGAN BEKU VAKUM - Purnamasari, Indah; Zamhari, Mustain; Putri, Shania (KINETIKA, 2021)
Coconut plants are multipurpose plants that have high economic value. Coconut tree is often referred as the tree of life because almost all parts of the tree, roots, stems, leaves and fruit can be used for the needs of everyday human life. Coconut dregs are a by-product of making coconut milk. In the past, coconut dregs were only used as animal feed and tempe bongkrek, whereas with a relatively small capital it can be processed into other products such as flour. The purpose of this study was to determine the best temperature for making coconut dregs flour using the Vacuum Freeze Drying method. This drying process is carried out with several temperature variations, which is -8 °C, -10 °C, -12 °C, -14 °C and variations in the weight of 100 and 200 gram of coconut dregs, as well as fixed variables using primary drying time of 6 hours, secondary drying 4 hours at a temperature of 50°C, and using a vacuum pressure of 70 cmHg. In determining the quality of coconut dregs based on the nutritional content of crude fiber, protein, fat and water that’s contained in the product, through the analysis with Kjedahl and Soxhlet methods.